Microstructural investigations on simulated intercritical heat-affected zone of boron modified P91-steel. Issue 13 (1st September 2020) - Khajuria, Akhil; Akhtar, Modassir; Bedi, Raman; Kumar, Rajneesh; Ghosh, Mainak; Das, C. R.; Albert, Shaju K.
Abstract : Conventional P91 and boron modified P91-steels were considered in the present investigation. Using Gleeble, weld intercritical heat-affected zone (ICHAZ) was processed. Conventional microscopy was done along with electron back-scattered diffraction for both specimens. Lath boundary of martensite was more, and preferably oriented for P91B-ICHAZ than P91-ICHAZ. Lattice strain was high and lath mobility was low for P91B-ICHAZ in comparison to P91-ICHAZ. Large fraction of ferritic grain structure (39.1%) and small fraction of fresh martensitic grain structure (9.5%) in P91-ICHAZ, whereas small fraction of ferritic grain structure (10.7%) and large fraction of fresh martensitic grain structure (32.7%) in P91B-ICHAZ was observed. However, tempered martensite exhibited meager variation. These differences between ICHAZ simulations were attributed to the presence of 100ppm-boron in P91B-steel.